U-Th-Pb systematics of opaline silica: Implications for the dating of surface processes - Simons, Suzanne Lee (Curtin University, 2015)
U–Pb and U-series analyses of U-rich, relative to both Th and Pb, opal samples using sensitive high-resolution ion microprobe (SHRIMP) demonstrate the ability of this technique for dating opals with ages ranging from several tens of thousands of years to millions of years and from a variety of deposition environments. This experimental study increases the understanding of opal as a geochronometer and explores the stability of U-Th-Pb systematics in opaline silica.